Research on livelihood strategy choices and influencing factors of farmers in the area of the Grain for Green Project in China - Ling, Shiquan; Yin, Zhu; Hu, Chao; Dong, Jiayun (Frontiers in Sustainable Food Systems, 2025)
Understanding the livelihood strategy choices and influencing factors of farmers in the area of GGP is conducive to improving the livelihood level of farmers in the area and promoting the quality and efficiency of the project. For this study, we combine the characteristics of farmers in the area of GGP, constructs a livelihood evaluation index system for farmers, and uses a binary logistic model to explore the influencing factors of farmers’ livelihood strategy choices. The research found: (1) The livelihood capital of farmers is ranked from high to low as part-time agricultural type (0.183), non-agricultural type (0.174), and pure agricultural type (0.126). (2) The stability level of farmers’ livelihoods is ranked from high to low as part-time agricultural type (0.607), non-agricultural type (0.519), and pure agricultural type (0.409). (3) The impact of livelihood capital on the livelihood strategy choices of different types of farmers varies significantly. The quality of economic forest site and the health status of the head of household is positively affecting the part-time agricultural type, negatively affecting pure agricultural type; Productive assets are positively affecting pure agricultural type, negatively acting on non-agricultural type, while labor is opposite. It is recommended that the government needs to pay attention to changes in farmers livelihoods after the expiration of the subsidy for GGP, and develop differentiated livelihood level improvement policies based on the characteristics of farmers’ livelihood capital.